Gene Expression Profiling of the Liver and Lung in Mice After Exposure to ZnO Quantum Dots - Yang Y; Li P; Lin Y; Li Z; Cui T; Song Z; Wu W; Lv S; Ji S (International Journal of Nanomedicine, 2020)
Yanjie Yang, Peisen Li, Yao Lin, Ziqi Li, Tianyi Cui, Zhenhua Song, Weixia Wu, Shuangyu Lv, Shaoping Ji Henan Provincial Engineering Centre for Tumor Molecular Medicine, Institute of Molecular Medicine, School of Basic Medical Sciences, Henan University, Kaifeng 475004, People’s Republic of ChinaCorrespondence: Shuangyu Lv; Shaoping JiSchool of Basic Medical Sciences, Henan University, Kaifeng 475004, People’s Republic of ChinaTel/Fax +86 371 2388 0585Email shuangyulv@henu.edu.cn; shaopingji@henu.edu.cnIntroduction: ZnO quantum dots (QDs) have drawn much attention recently as they are Cd-free, low-cost, and have excellent optical properties. With the expanded production and application of ZnO nanoparticles, concerns about their potential toxicity have also been raised.Materials and Methods: We used RNA sequencing (RNA-seq) to analyze the global gene expression of liver and lung tissues after ZnO QDs treatment. Differentially expressed genes (DEGs) were screened, with a fold change > 1.5 and padj < 0.05. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were performed, and padj < 0.05 was considered significantly enriched. The RNA-seq results were validated by quantitative real-time polymerase chain reaction (qRT-PCR).Results: A total of 47 and 218 genes were significantly differentially expressed in the liver and lung. Eight GO terms were enriched in the liver and lung, and retinol metabolism and the peroxisome proliferator-activated receptor (PPAR) signaling pathway were shared in different tissues.Discussion: According to DEGs and pathway enrichment analyses, inflammation might be induced in liver and lung tissues after intravenous injection of ZnO QDs. These findings will be helpful for future research and application of ZnO QDs.Keywords: ZnO QDs, transcriptome, differentially expressed genes